ANALISIS EFEKTIVITAS MODAL KERJA DALAM MENINGKATKAN PROFITABILITAS PADA PT KIMIA FARMA (PERSERO) TBK - Silvi Primata Putri; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to determine the effectiveness of working capital in increasing profitability at PT Kimia Farma (Persero) Tbk. The collection techniques used in this study were documentation and interviews. Data obtained in the form of secondary data. The data analysis technique used is descriptive statistical method.                              From the results of data analysis research using the activity ratio with indicators of cash turnover, accounts receivable turnover, inventory turnover, and working capital turnover has decreased and as a whole can be categorized ineffective. As for profitability ratios with indicators of gross profit margin (GPM), return on assets (ROA) and return on equity (ROE) fluctuate and can be categorized as ineffective as a whole. But to produce a gross profit the company has been said to be effective because it is able to produce a gross profit margin (GPM) above the industry average. Keywords: Effectiveness, Working Capital, Profitability